From residing in solidarity between people living from work to life in urban-rural residential complexes - González-Serna, Aura (Prospectiva. Revista de Trabajo Social e Intervención Social, 2016)
This article enquires on the sociological and spatial transformations that favor the development of the periphery of Medellin city in Colombia. Focusing on areas where historically settled down people classified on levels 1, 2 and 3. On the XXI century, the use of different techniques has disregarded nature looking for the efficient management of space and the use of public spaces for business purposes.The main objective of this policy is the massive supply of social housing in vertically oriented projects, it means flats in residential compounds, which implies the payment of administrations feeds. This sort of planning where capital plays an important role which aim was to raise the quality of life of people involved in the project, has convey to contradictory expectations for each other. Medellin is today a fragmented city standardized by locations. There is no project involving the preservation of people’s life and instead what we observe is a project of a city full of attractive areas for tourism and international events while culture is completely forgotten.